Alzheimer's brain changes - Cheah, Pike See; Tan, Niu Jin; Vidyadaran, Sharmili; Nordin, Norshariza; Baharuddin, Mohd Nasir; Lim, Chai Ling; Mohamed Seth, Eryse Amira; Ling, King Hwa (Universiti Putra Malaysia Press, 2016)
Alzheimer’s disease (AD) is a neurodegenerative condition that is predominant in the elderly, making it a major cause of disability. Gradual loss of brain cells is a feature of AD, causing memory loss and decline in cognitive functions including judgment, attention, and learning. The progression of AD is attributed to the build-up of abnormal structures such as plaques and tangles, eventually leading to death of brain cells.